ANALISIS TENTANG PARLIAMENTARY THRESHOLD DAN CALON PERSEORANGAN BERDASARKAN UNDANG-UNDANG NOMOR 10 TAHUN 2016 DALAM PERSPEKTIF DEMOKRASI DAN PRINSIP CHECK AND BALLANCES - Surya Darma Kardeli (Faculty of Law, University of Muhammadiyah Malang, 2018)
The application of the parliamentary threshold in the conduct of the elections is still a problem for political parties. Determination of the limits of the requirements to be met by political parties to be able to register candidates as set forth in the provisions of article 40 paragraph (1) of Act No. 2016 10 years about the election of the Governor, Governor and Mayor, was by fulfilling the most gains of at least 20% of the total area of the House of representatives seats or 25% of the accumulated gains of legitimate votes in the general election of members of the House of representatives in the Regions concerned. In addition, the mechanism of elections nowadays also provides the opportunity for individual candidates to be able to advance in the implementation of the elections. This is a real form of the implementation of the people's democracy, due to the demands of the people to get the leaders of his country who have the attitude that aspirational, competent, legitimate and not just think of the interests of political parties. But in fact, the spirit of democracy through mechanisms of individual candidates much have obstacles, one of which is to embody the principle of checks and balances in the Organization of the functions of Government. Based on the above description, then the legal research is trying to give the explanation with regard to whether the reason that the application of parliamentary threshold in the law No. 10 The year 2016 could hinder the implementation of democracy and how are the dynamics of the working relationship between parliament and the prospective head of the area of an individual who is not capable of embodying the principle of checks and balances. This study derives the conclusion that implementation the parliamentary threshold in the conduct of the elections could hinder the implementation of democracy because it is contrary to the laws and regulations and may also harm the justice the coveted by society and are protected by the Constitution of 1945. With regard to the inability to realize the principle of checks and balances in the relationship between Government function of organizing local and regional head of individual candidates that caused a political attitude which parliament does not provide support politics to the head area of an individual.